PENGEMBANGAN E-MODUL SISTEM PENCERNAAN MANUSIA TERINTEGRASI NILAI KEISLAMAN UNTUK PESERTA DIDIK KELAS VIII SMP - Amiranda, Natasya; Hakim, Nasrul (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Learners can engage in modules to autonomously review and assimilate Islamic qualities. By understanding the connection between biological material and Islamic values, the goal is for students to have a strong religious foundation. Apart from that, the module must also be adapted to current developments, especially the need for electronic development (e-module). The motivation for this research is to observe and see opportunities for introducing material in the form of e-modules combined with Islamic characteristics. The ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model is used in this development research, which refers to R&D (Research & Development) research. This development stage consists of a validation and revision process. This approval cycle occurred twice, and this approval stage was assisted by two experts (one media expert and one material expert), testing in small groups (13 students) and one science teacher. The purpose of validation is to ensure whether the product being developed can be achieved or not. The human digestive system e-module developed in integration with Islamic values is suitable for use in science learning activities on the human digestive system material based on the design appearance of 82%, the material content of 91%, teacher response of 88%, and student response of 69%.